(untitled) - Gene Berryhill (Albany, New York, 2000)
This books covers the creation and handling of graphics for the World Wide Web, including image management strategies, compression, palettes, graphic creation and manipulation, conversion, working with display text, simple animations, and Photoshop's "onionkinning" techniques for animation.
Keywords: web sites,world wide web ( information retrieval system )